Frequency of Adverse Event Monitoring in Ambulatory Patients on Amiodarone or Dofetilide. (October 2018) - Rickard, Joshua P.; Negrelli, Jenna; Olson, Jeffery L.; Dick, Travis
Background: Published studies state that adherence to regular laboratory assessments for anti-arrhythmic drugs is as low as 20%. Monitoring adherence is important as other studies have shown that up to 93% of patients on amiodarone experience an adverse drug event leading to a potentially lethal event. Objective: To determine whether patients prescribed amiodarone or dofetilide are being monitored according to package labeling and guideline recommendations for adverse events. Methods: Patients prescribed amiodarone or dofetilide from a 2-year period were eligible for inclusion. Patients with ventricular arrhythmias, prescribed more than 1 anti-arrhythmic agent, or received anti-arrhythmic monitoring outside the health-care system were excluded. Adherence to monitoring parameters was assessed according to labeled recommendations and published guidelines. The primary objective was to determine the frequency of baseline and follow-up monitoring recommendations for patients receiving amiodarone or dofetilide. The secondary objective was to determine rates of adverse drug events. Results: One hundred patients were evaluated (amiodarone n = 50, dofetilide n = 50). Average rates of baseline and follow-up amiodarone monitoring parameters were 55% and 57%, respectively. Average rates of baseline and follow-up dofetilide monitoring were 99.6% and 85%, respectively. There was a statistically significant difference in abnormally elevated thyroid-stimulating hormone levels (8%-30%, P ≤ .005) after patients were prescribed amiodarone. Twelve percent of patients taking dofetilide had an increase in QTc interval by >15%. Conclusions: Amiodarone adverse event monitoring was lower than dofetilide in this cohort. Improving the monitoring of these agents may decrease morbidity risk in this population.